2022
DOI: 10.3390/ijms231810258
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a High-Density Recombination Bin-Based Genetic Map Facilitates High-Resolution Mapping of a Major QTL Underlying Anthocyanin Pigmentation in Eggplant

Abstract: High-density genetic maps can significantly improve the resolution of QTL mapping. We constructed a high-density recombination bin-based genetic map of eggplant based on 200 F2 plants from an interspecific cross (Solanum melongena × S. incanum) using the whole genome resequencing strategy. The map was 2022.8 cM long, covering near 99% of the eggplant genome. The map contained 3776 bins, with 3644 (96.5%) being effective (position non-redundant) ones, giving a nominal average distance of 0.54 cM and an effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“…Anthocyanin pigmentation has been a key trait in quantitative trait locus (QTL) studies since the very first molecular linkage maps were developed for eggplant [ 47 , 48 ]. Over the last ten years, a succession of QTL analyses performed with ever-increasing numbers of molecular markers have revealed that regions on two chromosomes are responsible for much of the variation in anthocyanin accumulation in eggplant tissues [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ].…”
Section: Eggplantmentioning
confidence: 99%
See 3 more Smart Citations
“…Anthocyanin pigmentation has been a key trait in quantitative trait locus (QTL) studies since the very first molecular linkage maps were developed for eggplant [ 47 , 48 ]. Over the last ten years, a succession of QTL analyses performed with ever-increasing numbers of molecular markers have revealed that regions on two chromosomes are responsible for much of the variation in anthocyanin accumulation in eggplant tissues [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ].…”
Section: Eggplantmentioning
confidence: 99%
“…The recent availability of an annotated eggplant genome sequence has also allowed researchers to identify candidate genes on eggplant chromosome 10. An amino acid substitution in a WD repeat-containing protein seems to underlie an E10.1 QTL controlling fruit pericarp color [ 57 ]. WD proteins are critical components of the MBW transcription factor complex that regulates anthocyanin biosynthesis.…”
Section: Eggplantmentioning
confidence: 99%
See 2 more Smart Citations
“…In most cases, genetic markers are no longer the limiting factor for genetic mapping; instead, the number of recombination events within the population is the limiting factor. Guan et al resequenced 200 F2 eggplants from an interspecific cross ( Solanum melongena × S. incanum ) for the construction of a recombinant bin map [ 8 ]. Using the phenotypic data of 172 F2:3 lines and this recombinant bin map, a major quantitative trait locus (QTL) was identified corresponding to the leaf vein color and fruit pericarp color.…”
mentioning
confidence: 99%